Years of life lost associated with COVID-19 deaths in the United States - Quast, Troy (J Public Health (Oxf), 2020)
BACKGROUND: The mortality effects of COVID-19 are a critical aspect of the disease’s impact. Years of life lost (YLLs) can provide greater insight than the number of deaths by conveying the shortfall in life expectancy and thus the age profile of the decedents. METHODS: We employed data regarding COVID-19 deaths in the USA by jurisdiction, gender and age group for the period 1 February 2020 through 11 July 2020. We used actuarial life expectancy tables by gender and age to estimate YLLs. RESULTS: We estimated roughly 1.2 million YLLs due to COVID-19 deaths. The YLLs for the top six jurisdictions exceeded those for the remaining 43. On a per-capita basis, female YLLs were generally higher than male YLLs throughout the country. CONCLUSIONS: Our estimates offer new insight into the effects of COVID-19. Our findings of heterogenous rates of YLLs by geography and gender highlight variation in the magnitude of the pandemic’s effects that may inform effective policy responses.